Nuclear import of LIKE HETEROCHROMATIN PROTEIN1 is redundantly mediated by importins α‐1, α‐2 and α‐3. (1st June 2020) - Chen, Chong; Kim, Daewon; Yun, Hee Rang; Lee, Yun Mi; Yogendra, Bordiya; Bo, Zhao; Kim, Hae Eun; Min, Jun Hong; Lee, Yong‐Suk; Rim, Yeong Gil; Kim, Hyun Uk; Sung, Sibum; et al.
Summary: LIKE HETEROCHROMATIN PROTEIN1 (LHP1) encodes the only plant homologue of the metazoan HETEROCHROMATIN PROTEIN1 (HP1) protein family. The LHP1 protein is necessary for proper epigenetic regulation of a range of developmental processes in plants. LHP1 is a transcriptional repressor of flowering‐related genes, such as FLOWERING LOCUS T ( FT ), FLOWERING LOCUS C ( FLC ), AGAMOUS ( AG ) and APETALA 3 ( AP3 ). We found that LHP1 interacts with importin α‐1 (IMPα‐1), importin α‐2 (IMPα‐2) and importin α‐3 (IMPα‐3) both in vitro and in vivo . A genetic approach revealed that triple mutation of impα‐1, impα‐2 and impα‐3 resulted in Arabidopsis plants with a rapid flowering phenotype similar to that of plants with mutations in lhp1 due to the upregulation of FT expression. Nuclear targeting of LHP1 was severely impaired in the impα triple mutant, resulting in the de‐repression of LHP1 target genes AG, AP3 and SHATTERPROOF 1 as well as FT . Therefore, the importin proteins IMPα‐1, ‐2 and ‐3 are necessary for the nuclear import of LHP1. Significance Statement: We describe the importance of nuclear import of LIKE HETEROCHROMATIN PROTEIN1 (LHP1), which acts as transcriptional regulator. Mis‐nuclear targeting of LHP1 causes severe growth defects and very early flowering. Importin alpha (IMPα) proteins bind to proteins that contain nuclear localization signals and help them to pass through the nuclear pore from cytoplasm to nucleus. There are 10 members of the IMPα family in the Arabidopsis genome but only IMPα‐1, ‐2 and ‐3 are involved in nuclear import of LHP1.